2006
DOI: 10.1038/nrmicro1325
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial-resistant bacteria in the community setting

Abstract: Over the past decade, antimicrobial resistance has emerged as a major public-health crisis. Common bacterial pathogens in the community such as Streptococcus pneumoniae have become progressively more resistant to traditional antibiotics. Salmonella strains are beginning to show resistance to crucial fluoroquinolone drugs. Community outbreaks caused by a resistant form of Staphylococcus aureus, known as community-associated meticillin (formerly methicillin)-resistant Staphylococcus aureus, have caused serious m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
192
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(200 citation statements)
references
References 131 publications
0
192
0
3
Order By: Relevance
“…The exact mechanism underlying our finding, though remains to be elucidated, may represent an example of the so-called 'collateral damage,' a term referring to the ecological adverse effects of antibiotic therapy, 71 which is believed to be driven largely by antibiotic selection pressure, and promoted by the spreading of plasmid-mediated antimicrobial-resistant genes within the progeny strains or unrelated resistant strains. 72,73 As mentioned earlier, fluoroquinolone is one of the most common agents linked to this collateral damage, that is, the emergence of various kinds of pathogens. [21][22][23][24][25][27][28][29][30][31][32][33][34][35][36][37][38]71 However, the patterns of emergence vary among studies; no single study has demonstrated the impact of fluoroquinolone use on all of the specific antibiotic-resistant patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism underlying our finding, though remains to be elucidated, may represent an example of the so-called 'collateral damage,' a term referring to the ecological adverse effects of antibiotic therapy, 71 which is believed to be driven largely by antibiotic selection pressure, and promoted by the spreading of plasmid-mediated antimicrobial-resistant genes within the progeny strains or unrelated resistant strains. 72,73 As mentioned earlier, fluoroquinolone is one of the most common agents linked to this collateral damage, that is, the emergence of various kinds of pathogens. [21][22][23][24][25][27][28][29][30][31][32][33][34][35][36][37][38]71 However, the patterns of emergence vary among studies; no single study has demonstrated the impact of fluoroquinolone use on all of the specific antibiotic-resistant patterns.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Klebsiella pneumonie have become resistant against cephalosporins and carbapenems, Escherichia coli against cephalosporins and fluoroquinolones, and Staphylococcus aureus adapts rapidly to acquire resistance against penicillin, methicillin, tetracycline, and erythromycin. 2 It is clear from the above that there is an ongoing need in developing new antimicrobial agents. In this sense, antimicrobial polymers offer a high versatility for avoiding microbial contaminations or infections.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4, 6, 7, and 17). The rapid evolution of drug resistance among bacterial pathogens is today a major clinical problem (23,24), and the reports on slow drug resistance evolution are important in that they suggest a combination of efflux pump inhibitory drugs and growth inhibitory drugs as a future strategy for effective treatment of bacterial disease with minimal risk of target resistance development (6). One reason for the slowing down of target resistance emergence by drug efflux pump deficiency may simply be the greatly enhanced drug susceptibility that arises by drug efflux inhibition (6).…”
Section: Target Resistance Masking and The Evolution Of Drug Resistancementioning
confidence: 99%